1962
DOI: 10.1103/physrevlett.9.489
|View full text |Cite
|
Sign up to set email alerts
|

High-Field Superconductivity in Niobium

Abstract: that the energy gap E and the cyclotron mass m^ at the bottom of the band are the same as those in pure bismuth, a Fermi energy in Bi 95 Sb 5 is calculated to be Eg =0.007 eV. The values for the Fermi energy and Eg in pure bismuth are taken to be those measured by Brown, Mavroides, and Lax in magnetoreflection measurements. 9 They are E e = 0.025 eV and E g = 0.015 eV. The number of electrons per ellipsoid is derived from Eq. (2) to bewhere m^detajy)" 113 is the density-of-states effective mass at the bottom o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1963
1963
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 6 publications
2
30
0
Order By: Relevance
“…The phenomenon just described has been noticed before. 6 The agreement between our results and those presented in A thorough theoretical description of the situation has not been advanced, and "a discussion of the physical explanation of our results will be postponed until "a better experimental picture can be developed and an applicable theory can be found. During the next report period, experimental work will proceed -6- shown, the sample has superconducting properties in fields larger than the critical field for bulk lead at that temperature.…”
Section: Methodssupporting
confidence: 64%
“…The phenomenon just described has been noticed before. 6 The agreement between our results and those presented in A thorough theoretical description of the situation has not been advanced, and "a discussion of the physical explanation of our results will be postponed until "a better experimental picture can be developed and an applicable theory can be found. During the next report period, experimental work will proceed -6- shown, the sample has superconducting properties in fields larger than the critical field for bulk lead at that temperature.…”
Section: Methodssupporting
confidence: 64%
“…As we observe, the H mag c2 (T ) line coincides entirely with the PE line H res peak (T ). This has been observed not only in Nb [54,55,56], but also in MgB 2 [42] superconductor.…”
Section: Phase Diagram Of Vortex Matter For Nb−2 Comparison With Thementioning
confidence: 99%
“…First, a local peak at T onset , and second a dip at T peak . This is the well-known PE in the critical current J c (the minimum in the measured voltage corresponds to a maximum/peak in the critical current J c ), which was observed in high-T c compounds [4,17,18,51], in superconductors of intermediate-T c as pristine and Carbon-doped MgB 2 [42,52,53], in Nb [9,10,54,55,56] and other low-T c [4,57,58,59] disordered superconductors. The comparison to our magnetic measurements (not shown here) revealed that the PE almost coincides with the upper-critical fields (see fig.…”
Section: Magnetoresistance Measurements and The Peak Effectmentioning
confidence: 99%
“…The sample was characterized by T c = 18.2 K, ΔT c = 0.1 K, T m = 38.84 K. A value of H c2 (0) = 22.2 T was extrapolated using the GLAG theory [20]. The Peak Effect measurements reported in literature were performed using various experimental techniques [7,10,[21][22][23][24][25]. The technique used in the present paper is based on the observation of a dip in the real part of the 1 st harmonics of the AC magnetic susceptibility, ' 1 χ [23].…”
mentioning
confidence: 99%